2017
DOI: 10.1007/s10517-017-3624-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Effects of Nanodispersed Ceria on Wound Repair

Abstract: We studied the effects of nanodispersed ceria on wound healing in vitro and in vivo. It was found that cerium dioxide stimulated wound healing, which manifested in shrinkage of burn wound area (by 1.5 times) and intensification (by 2.4 times) marginal epithelialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…NPs exert an anti-inflammatory response both in the blood plasma, as previously shown in chapter 3.3, and capsule tissue. Similar results were also obtained by Legon`kova et al and Gong et al in wound repair, where they showed that Ce-based nanomaterials stimulate the wound healing and epithelial regeneration process in the presence of lymphocyte-macrophage infiltration (Legonkova et al, 2017;Gong et al, 2022).…”
Section: Increase In Macrophage Recruitment After Np Treatment As Dem...supporting
confidence: 86%
“…NPs exert an anti-inflammatory response both in the blood plasma, as previously shown in chapter 3.3, and capsule tissue. Similar results were also obtained by Legon`kova et al and Gong et al in wound repair, where they showed that Ce-based nanomaterials stimulate the wound healing and epithelial regeneration process in the presence of lymphocyte-macrophage infiltration (Legonkova et al, 2017;Gong et al, 2022).…”
Section: Increase In Macrophage Recruitment After Np Treatment As Dem...supporting
confidence: 86%
“…Today, cerium oxide nanoparticles (nanoceria, CeNPs) are considered one of the most promising metal oxide nanobiomaterials [19][20][21][22]: pristine (bare) or ligand-stabilized CeNPs are well-known therapeutic agents in regenerative medicine [19][20][21][22] and tissue engineering [22]; they stimulate the proliferation of cells in vitro [21,23,24] and accelerate the healing of lesions in vivo [25], thus reshaping perspectives for wound therapy [26,27]. CeNPs have been shown to be the first inorganic mitogen: in 2019, Popov et al reported experimental evidence for the mitogenic action of CeNPs in the regeneration of a whole organism, freshwater flatworms [28].…”
Section: Multifaceted Biomedical Applications Of Cerium Oxide Nanoparmentioning
confidence: 99%
“…CNPs as bioactive materials have been introduced as remarkable therapeutics for skin tissue repair and regeneration [ 99 , 100 ]. Nanoceria is recognized as a stimulator of fibroblast proliferation in vitro [ 101 , 102 ] and an accelerator of the healing of model lesions in vivo [ 103 , 104 ]. Having unique antioxidant, anti-inflammatory, and antibacterial properties, CNPs have attracted much attention for use in the treatment of both acute (e.g., burns) and chronic (diabetic wounds) skin lesions.…”
Section: Nanoceria For Soft-tissue Engineeringmentioning
confidence: 99%